Clinical Placement Amidst the Covid-19 Pandemic: An Exploration of Nursing Students' Emotional Experiences and Response Strategies - Rantung, Gilny Aileen Joan; Rosmawati, Rina (Devotion : Journal of Research and Community Service, 2023)
The nursing education and clinical placement programs, along with healthcare systems globally, have been substantially affected by the Covid-19 pandemic. This study explores the emotional experiences and response strategies of nursing students during clinical placement amidst the Covid-19 pandemic in Indonesia. Fourteen nursing students in their final year participated in the study. The study identified two main themes and associated subthemes: emotional responses (including fear, anxiety, uncertainty, and confidence) and coping strategies (including maintaining physical health, adhering to safety protocols, maintaining a positive outlook, nurturing spiritual well-being, and building self-confidence). The emotional responses highlight the challenges faced by nursing students during clinical placement, particularly fear and anxiety about contracting the virus, uncertainty, and confusion. However, some students also felt confident in their ability to navigate the challenges of clinical placement and had a sense of duty and purpose in serving their patients during the pandemic. Coping strategies employed by nursing students included maintaining physical health, adhering to safety protocols, maintaining a positive outlook, nurturing spiritual well-being, and building self-confidence. The study underscores the importance of recognizing and addressing the emotional impact of the pandemic on nursing students and the need for effective support mechanisms to help them cope with the challenges of clinical practice. Educational programs that promote mental health and well-being and practical training on infection control and safety protocols can help nursing students cope with the challenges of clinical placement during pandemics.